The business case for vertical farming in South Africa - Madima, Andani Eric (My University, 2018)
Food security means that there is a sufficient supply of and access to safe and nutritious food. As the population continues to grow, arable land diminishes due to soil erosion and degradation, and fuel prices rise, food security is threatened. It is critical now more than ever that a new system of food production be developed if we are to sustain and improve our way of living and ensure that food security reduces vulnerability to famine. The vertical farming (VF) concept is one way to achieve this, and it is about maximising plant density to allow people in urban environments to access healthy, fresh produce all year round, that is free from harmful chemicals like herbicides and pesticides, and protected from bacteria like E. coli., listeria, and salmonella. Furthermore, VF produces up to 100 times more produce, uses 70-95% less water, and has cheaper operational costs than conventional farming methods. Elysium (Pty) Ltd is a company that plans to revolutionise the way food is produced by bringing the farms directly to the consumer in the form of innovative buildings, called eHouses. The first eHouse will be established in Cape Town due to its high GDP per capita, the ensuing water crisis, and the extensive distances (as much as 1800km) travelled by producers to reach consumers. A 2,560 m² warehouse has been selected to house production, where a controlled- environment agriculture (CEA) technology from the United States will be used to facilitate the production of microgreens, cucumbers, tomatoes, and lettuce. The CEA technology promises to produce up to 1200x the yield obtained from conventional farming methods. The produce will be distributed through chain stores, the Cape Town Fresh Produce Market, and deliveries made directly to customers, through a 70%, 20%, 10% split, respectively. The chosen target market is persons of Social Economic Measure (SEM) 8-10 due to the numerous added benefits Elysium’s produce provides over competitors. A total capital investment of R46.7m is required, with a Net Present Value (NPV) of R19.83m over a 10-year period. The break-even point is 5 years, with an Internal Rate of Return (IRR) of 28%, which is well above the Weighted Average Cost of Capital (WACC) of 12.29%.
MBA
Keywords: Food industry and trade -- South Africa. Agriculture -- Economic aspects -- South Africa. Organic farming -- South Africa.